Identification of BRCA2 Cis Double Heterozygous Breast Cancer Cases Using Whole Exome Sequencing: Phenotypic Expression and Impact on Personalized Oncology - Hamdi, Yosr; Boujemaa, Maroua; Mighri, Najah; Mejri, Nesrine; Jaidane, Olfa; Ben Nasr, Sonia; Bouaziz, Hanen; Hassouna, Jamel Ben; Zribi, Aref; Berrazaga, Yossra; Rachdi, Haifa; Daoud, Nouha; et al. (Frontiers in Genetics, 2021)
BRCA1 and BRCA2 are the most commonly mutated breast cancer susceptibility genes that convey a high risk of breast and ovarian cancer. Most BRCA1 or BRCA2 mutation carriers have inherited a single heterozygous mutation. In recent years, very rare cases with biallelic or trans double heterozygous mutations on BRCA1 and or BRCA2 have been identified and seem to be associated with distinctive phenotypes. Given that this genotype-phenotype correlation in cancer-predisposing hereditary conditions is of relevance for oncological prevention and genetic testing, it is important to investigate these rare BRCA genotypes for better clinical management of BRCA mutation carriers. Here we present the first report on Cis double heterozygosity (Cis DH) on BRCA2 gene identified using Whole exome sequencing (WES) in a Tunisian family with two BRCA2 mutations namely: c.632-1G>A and c.1310_1313DelAAGA that are both reported as pathogenic in ClinVar database. Subsequent analysis in 300 high-risk Tunisian breast cancer families detected this Cis double heterozygous genotype in 8 additional individuals belonging to 5 families from the same geographic origin suggesting a founder effect. Moreover, the observed Cis DH seems to be associated with an early age of onset (mean age = 35.33 years) and severe phenotype of the disease with high breast cancer grade and multiple cancer cases in the family. The identification of unusual BRCA genotypes in this Tunisian cohort highlights the importance of performing genetic studies in under-investigated populations. This will also potentially help to avoid erroneous classifications of genetic variants in African population and therefore avoiding clinical misdiagnosis of BRCA related cancers. Our findings will also have an impact on the genetic testing and the clinical management of North African breast cancer patients as well as patients from different other ethnic groups in regard to several emerging target therapies such as PARP inhibitors.